High-order harmonic generation driven by inhomogeneous plasmonics fields spatially bounded: influence on the cut-off law. (25th January 2018) - Neyra, E; Videla, F; Ciappina, M F; Pérez-Hernández, J A; Roso, L; Lewenstein, M; Torchia, G A
Abstract: We study high-order harmonic generation (HHG) in model atoms driven by plasmonic-enhanced fields. These fields result from the illumination of plasmonic nanostructures by few-cycle laser pulses. We demonstrate that the spatial inhomogeneous character of the laser electric field, in a form of Gaussian-shaped functions, leads to an unexpected relationship between the HHG cutoff and the laser wavelength. Precise description of the spatial form of the plasmonic-enhanced field allows us to predict this relationship. We combine the numerical solutions of the time-dependent Schrödinger equation (TDSE) with the plasmonic-enhanced electric fields obtained from 3D finite element simulations. We additionally employ classical simulations to supplement the TDSE outcomes and characterize the extended HHG spectra by means of their associated electron trajectories. A proper definition of the spatially inhomogeneous laser electric field is instrumental to accurately describe the underlying physics of HHG driven by plasmonic-enhanced fields. This characterization opens up new perspectives for HHG control with various experimental nano-setups.